La colisión y prevalencia de los derechos fundamentales de la mujer y la protección jurídica al nasciturus: referencia a la jurisprudencia de E.E.U.U y Colombia. - Iglesias Camacho, Katerina (Universidad Antonio Nariño, 2023)
This degree work includes the most notable aspects of the collision and prevalence of women's rights, such as their right to reproductive self-determination, to life, health (mental and physical), freedom of conscience or privacy, and the legal protection of the life of the unborn child. For this purpose, initially the dogmatic criteria on the origin of the life of authors such as: Rivera Sierra, Juan La Cadena, Molina Betancourt, Dworkin and jurisprudence of the Constitutional Court of Colombia will be taken into account, which hold positions that are antagonistic to each other. Next, the different pronouncements adopted by international courts are analyzed, delving into the North American one, and specifically in paradigmatic cases that have marked the debate within the judiciary.